Correlación ecográfica del primer trimestre con la escala de Capurro para determinar las semanas de gestación del recién nacido. - Gómez Acosta, Almendra Ailed; Reyes Reyes, Alejandra Elizabeth; Ayón Aguilar, Jorge; Beltrán Romero, Cecilia Alejandra; Parada López, Julia Isis (Ginecología y Obstetricia de México, 2025)
OBJECTIVE: To determine the correlation between first trimester ultrasound and the Capurro scale for neonatal gestational weeks. MATERIALS AND METHODS: Longitudinal study carried out at the Hospital General de Zona 20 La Margarita, Puebla, Pue. Pregnant patients with a first trimester ultrasound performed by a radiologist and live newborns evaluated by a single paediatrician using the Capurro scale were included. Descriptive and inferential statistical techniques were applied using Spearman's Rho; values were considered statistically significant with a value ≤ 0.05. RESULTS: 341 patients were examined by Spearman's Rho correlation coefficient and a high positive correlation (r = 0.886), statistically significant (p = 0.000), was obtained between the first trimester ultrasound transposed to birth and the Capurro score given by the paediatrician. CONCLUSIONS: there is a correlation between the weeks of gestation determined by first trimester ultrasound and those obtained with the Capurro scale.